The GIP/GIPR axis in medullary thyroid cancer: clinical and molecular findings. Issue 5 (29th April 2022) - Regazzo, Daniela; Bertazza, Loris; Galletta, Eva; Barollo, Susi; Mondin, Alberto; Zovato, Stefania; Iacobone, Maurizio; Zilio, Eleonora; Scaroni, Carla; Radu, Claudia Maria; di Benedetto, Giulietta; Mian, Caterina; et al.
Abstract : The improper expression of glucose-dependent insulinotropic polypeptide receptor (GIPR) and the GIP/GIPR axis activation has been increasingly recognized in endocrine tumors, with a potential diagnostic and prognostic value. A high tumor-to-normal tissue ratio (T/N ratio) of GIPR was reported both in humans' and in rats' medullary thyroid cancer (MTC), suggesting a direct link between the neoplastic transformation and the mechanism of receptor overexpression. In this study, we evaluated the potential diagnostic and prognostic significance of GIPR expression in a large cohort of MTC patients by correlating GIPR mRNA steady-state levels to clinical phenotypes. The molecular effect of GIP/GIPR axis stimulation in MTC-derived cells was also determined. We detected GIPR expression in ~80% of tumor specimens, especially in sporadic, larger, advanced-stage cancers with higher Ki-67 values. GIPR stimulation induced cAMP elevation in MTC-derived cells and a small but significant fluctuation in Ca 2+, both likely associated with increased calcitonin secretion. On the contrary, the effects on PI3K-Akt and MAPK-ERK1/2 signaling pathways were marginal. To conclude, our data confirm the high T/N GIPR ratio in MTC tumors and suggest that it may represent an index for the degree of advancement of the malignant process. We have also observed a functional coupling between GIP/GIPR axis and calcitonin secretion in MTC models. However, the molecular mechanisms underlying this process and the possible implication of GIP/GIPR axis activation in MTC diagnosis and prognosis need further evaluation.